Paediatric tic-like presentations during the COVID-19 pandemic. Issue 3 (25th November 2021) - Buts, Sarah; Duncan, Morvwen; Owen, Tamsin; Martino, Davide; Pringsheim, Tamara; Byrne, Susan; McWilliams, Andrew; Murphy, Tara; Malik, Osman; Liang, Holan; Heyman, Isobel; Hedderly, Tammy
Abstract : Background and aim: Clinical centres have seen an increase in tic-like movements during the COVID-19 pandemic. A series of children and adolescents are described. Methods: A retrospective chart review of 34 consecutive paediatric patients presenting with sudden onset tic-like movements, seen over 6 months. Results: 94% of patients were female, with an average age of sudden onset or increase of tic-like movements of 13.7 years. 44% had a previous diagnosis of tics, and 47% initially presented to an emergency department. Comorbid psychiatric and neurodevelopmental disorders were reported in 91% with 68% reporting anxiety. Conclusion: We highlight a dramatic presentation of sudden onset functional tic-like movements in predominantly female adolescents to help inform identification and management. There is need to research the neurobiological underpinnings and environmental exacerbating factors leading to these presentations and to explore effective therapeutic strategies.